Ship-based Trackline Geophysical Data (MGD77) from the Drake Passage acquired during the Nathaniel B. Palmer expedition NBP0812 (2008) (IEDA: Marine-Geo Digital Library, 2009)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP0812 conducted in 2008 (Chief Scientist: Dr. Teresa Chereskin). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise. Data were acquired as part of the project(s): Dynamics and Transport of the Antarctic Circumpolar Current in Drake Passage, and funding was provided by NSF grant(s): ANT06-36493